Der Slawengau Besunzane im Licht der Ortsnamen - Wenzel, Walter (Universitätsbibliothek Leipzig, 2015)
The Slavic district Besunzane in the light of toponymy. – With the help of Slavic place-names Hans Walther was first in localizing the tribal region of the Besunzane in the area of the Neiße river between Görlitz and Ostritz. Based on this research the present article presents the previous findings with the aid of typology and stratigraphy of place-names more precisely. The quality values of the soil are thereby also taken into consideration. On the accompanying map with older and more recent Slavic place-names the region of Besunzane appears as a ca. 8 kilometer wide strip along the Neiße river, almost throughout on land with soil quality values lying over 50 points. In the west it is sharply separated by a broad unpopulated zone from the tribal region of the Milzane. By evidence of place-names, the strips of land to the east of Besunzane were sparsely populated, if at all, likewise in the south. To the north of Görlitz there are solely more recent types of place-names.